Simulation of the Potential Effect of Meteorological Condition Variations on Forage Production in Native Pastures in the Warm Climate of Colombia - Eliecer David Díaz-Almanza; José Alejandro Cleves-Leguizamo; Rodrigo Daniel Salgado-Ordosgoitia (Land)
The increasing variability of climatic conditions poses significant challenges for agricultural and livestock systems worldwide. In regions with warm climates, such as northern Colombia, the effects of changing temperature, precipitation, and evapotranspiration are particularly pronounced, influencing the productivity and sustainability of native pastures. To address these challenges, modeling tools provide a valuable means of understanding and predicting forage production dynamics under diverse climatic scenarios, enabling farmers to make informed decisions that enhance resilience and sustainability. This research was conducted in Córdoba, Colombia, with the objective of evaluating the impact of climatic variations in temperature, precipitation, and evapotranspiration on forage production in native pastures in hot climates in northern Colombia. Modeling tools were used to assess the potential yield of pastures based on climate conditions, enabling the understanding and addressing of challenges associated with climatic fluctuations in estimated production. To plan animal grazing, climate variability from 2018 to 2021, a period influenced by the El Niño–Southern Oscillation (ENSO) phenomenon, was analyzed. This type of integrated analysis, which combines meteorological data, soil, crops, and evaluation of animal load per unit area, is an ideal and practical approach to addressing productivity challenges associated with climatic variability in livestock production in the warm climate of Colombia. The results confirmed the significant impact of climatic conditions on forage production, leading to the conclusion that simulation tools for water use in Bothriochloa “Colosuana” pastures are relevant for efficient water resource management, particularly during the dry season and drought events. This allows for anticipating the impacts of climate change on agriculture and livestock, facilitating timely and sustainable decision-making by farmers.